Financiación del servicio público de transporte urbano: Un estudio empírico en las empresas espa\~nolas - M. Luisa Delgado Jalón; Miguel A. Sánchez de Lara; Alba Gómez Ortega (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2014)
– The sensitivity in the public urban transport sector, focusing on a progressive improvement in the economic and technical management of passenger services and the need to design a transparent public finance system and according to the current economic circumstances, has led to increased interest and concern to improve the knowledge of its structure and evolution. This has encouraged the emergence of the conditions for the adoption of the initiative of the institutions that have promoted the creation of the Costs and Funding of Collective Urban Transport Watchdog (TUC Watchdog). The TUC Centre's objectives focus on the study of the operating conditions and financing of surface urban public transport concessions in Spain, through the generation of representative measures of behavior patterns, in order to enhance the real knowledge of the sector. In this paper, we present a study of the current problems in the financing of urban public transport in Spain, from the work carried out for the first report of the TUC (2008-2009).
Keywords: R40; R49; M49; 330; Passenger transport; Finance; Costs; Economic and financial analysis; Transport Watchdog